Halophytes as a rangeland resource - D Kelley (California Agriculture, 1984)
Not available – first paragraph follows: More than 40 million of California's 100 million acres are rangelands. The forest, grassland, and rangeland environments comprise about two-thirds of the land area of the state, and more than 50 million acres are grazed. The desert saltbush, an abundant, shrubby inhabitant of some of California's driest, saltiest rangelands, is one of many salt-tolerant shrubs, trees, and grasses that have become increasingly valuable as resources for arid and saline lands. These salt-tolerant plants (halophytes) provide forage for livestock and wildlife in range-lands throughout the West. Furthermore, many have been shown to be adaptable to genetic manipulation by selection or breeding.